Effect of educational intervention based on the theory of planned behavior (TPB) on amount of salt intake in pregnant women with PreHypertension - Moghaddam, Fatemeh Goldani; Hoseinzadeh-Chahkandak, Fatemeh; Salmani, Fatemeh; Norozi, Ensiyeh (BMC women's health, 2024)
Background Prehypertension is one of the common disorders during pregnancy. Reducing salt intake is among the best cost-effective interventions to reduce the risk of hypertension. The present study aimed to explore the effect of an educational intervention based on the Theory of Planned Behavior (TPB) on amount of salt consumed by prehypertensive pregnant women. Methods The present quasi-experimental study was conducted in 2022 on 61 prehypertensive pregnant women visiting the Comprehensive Health Services Centers in Birjand, Iran. Pregnant women were selected through a convenience sampling method and randomly assigned to intervention and control groups. A blood pressure test and a 24-hour urine test were taken in 3 stages (before, immediately after, and one month after the intervention). A reliable and valid questionnaire based on the TPB was used to measure the cognitive variables. The intervention program included three training sessions based on the TPB held on an online platform (WhatsApp social network). Data were analyzed using repeated measures ANOVA and longitudinal marginal model with the GEE approach in SPSS19. The significance level for all statistical tests was set at p < 0 0.05. Results After intervention, the mean score of perceived behavioral control ( p = 0.02), intention ( p = 0.004), and salt consumption behavior ( p = 0.03) increased significantly in the intervention group, and the mean score of systolic blood pressure ( p < 0.001) and diastolic blood pressure ( P < 0.01) decreased significantly in this group. In the control group, a statistically significant difference was observed in the systolic and diastolic blood pressure of the subjects ( p < 0.01). However, the score of attitude, subjective norms, perceived behavioral control, intention, salt consumption behavior and the daily salt intake did not show a statistically significant difference over time ( P < 0.05). Conclusion The present findings showed that the perceived behavioral control, intention, behavior, systolic and diastolic blood pressure can be modifiable variables to improve the amount of salt consumed by pre-hypertensive pregnant women. Therefore, we recommend that the present model be used to develop interventions to improve health indicators in pregnant women as a highly susceptible group in society.